"Improvement of Mechanical Properties of Reinforcing Steel Used in the Reinforced Concrete Structures" - Keleştemur, Oğuzhan; Keleştemur, M. Halidun; Yıldız, Servet (My University, 2009)
SAEIOIO structural carbon steel, which has a low cost price and wide range of use in the construction industry, has been studied as dual phase (DP) steel subjected to appropriate heat treatment, and its mechanical properties have been investigated under various tempering conditions. Intercritical annealing heat treatment has been applied to the reinforcing steel in order to obtain DP steels with different martensite volume fraction. In addition, these DP steels have been tempered at 200, 300 and 400 'C for 45 min and then cooled to the room temperature. Mechanical properties such as tensile strength, yield strength, reduction in cross-sectional area, total elongation, resilience modulus and toughness have been examined. Furthermore, fractographic examination has been done with scanning electron microscope (SEM) as well as metallographic examination of the steels. As a result of this study, it is found that mechanical properties of DP steel have changed according to the hardness and ratio of martensite phase. In addition, tensile strength, yield strength and resilience modulus of the steels have been reduced. In contrast, the total elongation, reduction of the cross-sectional area and toughness have been increased.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Dual-phase steel; Reinforcing steel; Tempering treatment; Mechanical properties